2021
DOI: 10.1101/2021.03.07.434269
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple bouts of high-intensity interval exercise reverse age-related functional connectivity disruptions without affecting motor learning in older adults

Abstract: Older adults show both age-related decreases in resting state functional connectivity and diminished sensorimotor function. Exercise has emerged as an intervention that may mitigate or even reverse these age-related declines. Here we sought to understand whether exercise impacts resting state functional connectivity, and motor acquisition and learning in older adults. Forty-two healthy older adults rested or completed 3 sets of high-intensity interval exercise (3 minutes at 75% maximal power output and 3 minut… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…Evidence from fMRI studies on physical activity demonstrated the changes in the activity of and functional connectivity between these network hub regions including the hippocampus, parahippocampus, dorsal anterior cingulate cortex (dACC), and ventromedial prefrontal cortex (vmPFC) that primarily subserve executive functions such as working memory, attention, and inhibition [15][16][17][18][19]. At the more system level, a 12month aerobic walking intervention was found to increase restingstate functional connectivity between subnetworks of DMN, and between subnetworks of SN [20], whereas connectivity in the CEN was found to increase after multiple sessions of high-intensity interval training [21]. Interestingly, the intensity of physical exercise appeared to modulate functional connectivity changes in the hub regions of the CEN [22], as well as in the DMN subsystems acutely and after 3 months of training [23].…”
Section: Potential Overlap Between Mental Health and Physical Activit...mentioning
confidence: 99%
“…Evidence from fMRI studies on physical activity demonstrated the changes in the activity of and functional connectivity between these network hub regions including the hippocampus, parahippocampus, dorsal anterior cingulate cortex (dACC), and ventromedial prefrontal cortex (vmPFC) that primarily subserve executive functions such as working memory, attention, and inhibition [15][16][17][18][19]. At the more system level, a 12month aerobic walking intervention was found to increase restingstate functional connectivity between subnetworks of DMN, and between subnetworks of SN [20], whereas connectivity in the CEN was found to increase after multiple sessions of high-intensity interval training [21]. Interestingly, the intensity of physical exercise appeared to modulate functional connectivity changes in the hub regions of the CEN [22], as well as in the DMN subsystems acutely and after 3 months of training [23].…”
Section: Potential Overlap Between Mental Health and Physical Activit...mentioning
confidence: 99%
“…31 The specificity of altered functional connectivity (FC) to SZ is being questioned. [32][33][34] Furthermore, it should be noted that exercise 35,36 and meditation 37 can affect resting-state FC.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise improves processing speed after stroke 7 with stroke. Data reported here are a subset of the larger study (Greeley et al, 2021;Neva et al, 2022).…”
Section: Participantsmentioning
confidence: 99%
“…Heart rate was recorded every three-minutes throughout the duration of the video. The serial targeting task was employed as the motor training task (Brodie et al, 2014;Mang et al, 2016;Greeley et al, 2021). Participants used their paretic arm to control a frictionless manipulandum to move a cursor between a start position and an end target projected by the Kinarm end-point robot (Kinarm, Kingston, ON, Canada).…”
Section: Controlmentioning
confidence: 99%
See 1 more Smart Citation